A study of household solid waste composition and generation at Taman Tas Kuantan Pahang - Nurliany , Abd. Rahman (2012)
The issues regarding the solid waste management is widely discussed, due to the increasing of waste generation, some problem related on insufficient of disposal landfill become government concern. Proper management need to implement in the future. Therefore, this research is undertaken to overview the management of solid waste at selected study area. The main objective listed by identifying the composition and generation of solid waste of populations. The research is covers on residential waste source at Taman Tas, Kuantan Pahang. There were two types of residential being study, Low Cost Housing Area and High Cost Housing Area. Survey study is conducted in order to determine the factors affecting the solid waste generation. The factors affecting waste generation can be identified by comparing both types of residential waste production. By calculation, the generation rate per person at High Cost Housing Area is 0.21 kg/day, which is higher compared to Low Cost Housing Area 0.18 kg/day. The analysis results suggested that, mainly the size of family was the factor influence the rate of solid waste generation and the socio-economic classification also influence the household waste generation. Food waste composition is found to be the most waste generated. In other hand, this paper briefly discuss the solid waste management at residential and the level of awareness among the respondents. Some suggestions are made to enhance the solid waste management at study area such as by providing facilities for waste segregation, the waste collector follow the schedule of waste collection route and conducted the awareness campaign at the residential area. Overall, there are no crucial problem arise at the study area.